The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2018 Solid-State, Actuators, and Microsystems Workshop Technical Digest 2018
DOI: 10.31438/trf.hh2018.13
|View full text |Cite
|
Sign up to set email alerts
|

Robust and Scalable Tissue-Engineerined Electronic Nerve Interfaces (Teeni)

Abstract: Peripheral nerves are excellent targets for neural interfaces designed to help amputees control prosthetic limbs. However, existing nerve interfaces have designs that significantly limit system performance. To overcome these limitations, we have combined micromachined neural interfaces with tissue-engineered hydrogel-based scaffolds. These tissue-engineered electronic nerve interfaces (TEENI) enable highly scalable nerve interfaces that provide significant interface-design freedom. The use of a hightemperature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…High lipid conditions due to obesity may be involved. Intraneural adipose cells are present inside nerves [ 43 ]. Reina et al examined the distribution of intraneural adipose cells in the sciatic nerve using a scanning electron microscope and reported that adipose tissue inside a nerve surrounded the fascicles to form adipose sheaths that separated the fascicles from one another [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…High lipid conditions due to obesity may be involved. Intraneural adipose cells are present inside nerves [ 43 ]. Reina et al examined the distribution of intraneural adipose cells in the sciatic nerve using a scanning electron microscope and reported that adipose tissue inside a nerve surrounded the fascicles to form adipose sheaths that separated the fascicles from one another [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…REMI allows for stable single-unit recordings for extended periods and has demonstrated successful recordings for almost a full year using biodegradable agarose scaffolds [95]. The tissue-engineered electronic nerve interface (TEENI) consists of thread-like arms in a biodegradable hydrogel scaffold, showing promising results with an excellent SNR in recording trials [96][97][98][99].…”
Section: Regenerative Electrodesmentioning
confidence: 99%
“…After only 4 days of implantation, the authors recorded single unit activity at the distal electrodes and were able to record electrophysiological activity over 6 weeks. 165 The TEENI was well integrated into the tissue with vascularization and axons throughout the scaffold. A more detailed immunohistochemical analysis was performed in another work and showed the presence of regenerated axons and Schwann cells but also a foreign body response related to the presence of the PI electrode threads.…”
Section: Biohybrid Interfacesmentioning
confidence: 99%
“…In a following work the TEENI was implanted in a damaged rat sciatic nerve with the distal and proximal nerves placed at the two ends of the device. After only 4 days of implantation, the authors recorded single unit activity at the distal electrodes and were able to record electrophysiological activity over 6 weeks . The TEENI was well integrated into the tissue with vascularization and axons throughout the scaffold.…”
Section: Biohybrid Interfacesmentioning
confidence: 99%